Enfin une loi-cadre des sociétés d'État au fédéral - Garant, Patrice (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
Bill C-24 relating to control of federal Crown corporations or State enterprises is among the best legacies of the Trudeau Administration. Federal State enterprises constitute an important economic empire that have caused some concern to many people over the last ten years. The Auditor General, the Commons Parliamentary Public Accounts Committee, the Lambert Commission on financial management and accountability, the Economic Council and other groups or individuals have made studies and proposals for reform. Three bills were introduced: C-29 by the Clark Government in 1979, C-123 in 1982 and C-153 in 1983 by the Trudeau Government ; all of them prior to bill 24 which has been a major innovation in the field of public law as it has introduced into the Financial Administration Act sixty sections dealing with the legal status of that which is so rightfully called the « Sociétés d'État » and with the ever so important question of controls exercised over them by Parliament and Government (Cabinet, Treasury Board, responsible minister and Finance Minister). Bill C-24 regulates over 400 institutions of the public economic sector, directly or indirectly. It is a major step towards the clarification of a branch of public law that has not yet reached a degree of sufficient maturity, coherence and fitness as to the objectives and needs of a political system that remains liberal and of an economy that is really a mixed economy.